2021
DOI: 10.26803/ijlter.20.5.9
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service Social Sciences Teachers’ Reflections on a Teacher Preparation Program

Abstract: The need for quality education in South Africa and beyond encourages research that interrogates the preparation of pre-service teachers and their ability to teach in the classroom after graduation. This qualitative paper focuses on the reflections of final year pre-service Social Sciences teachers in a South African public university. Gibbs’ reflective cycle is used as a lens. We used open-ended questions to gather data from 19 pre service Social Sciences teachers to explore their preparedness and readiness to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In addition, the literature argues for preservice teachers' preparedness for the teaching profession. Preservice training and preparation do not effectively prepare future teachers with limited knowledge, experiences, and exposure (Freeman et al, 2013;Nganga et al, 2020;Nwati & Thuthukile, 2021), and this hits teacher education institutions with various criticisms (Naylor et al, 2015). As such, it is imperative to look at the preservice teachers' preparation, especially in mathematical problemsolving, where limited local studies have been found.…”
Section: Preservice Teacher Training and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the literature argues for preservice teachers' preparedness for the teaching profession. Preservice training and preparation do not effectively prepare future teachers with limited knowledge, experiences, and exposure (Freeman et al, 2013;Nganga et al, 2020;Nwati & Thuthukile, 2021), and this hits teacher education institutions with various criticisms (Naylor et al, 2015). As such, it is imperative to look at the preservice teachers' preparation, especially in mathematical problemsolving, where limited local studies have been found.…”
Section: Preservice Teacher Training and Preparationmentioning
confidence: 99%
“…The worldwide demand for high-quality education emphasizes preservice teachers' attributes (Nwati & Thuthukile, 2021). Despite being hopeful that EPTs will enter the profession with a positive attitude toward mathematics teaching and learning (Ibañez & Pentang, 2021;Ray & Herron, 2021), the reports above prompted this study on the problem-solving performance of EPTs.…”
Section: Context Of the Studymentioning
confidence: 99%
“…It has been argued that prior learning experience influences preservice teachers' beliefs, views, and practices (e.g., Beauchamp & Thomas, 2009;Martin, 2008). Pre-service teachers who enter teacher education programs possess a range of perceptions and beliefs about teaching and learning and in this context, http://ijlter.org/index.php/ijlter reflection is considered to be a key component in teacher education programs (Hatton & Smith, 1995;Nwati & Thuthukile, 2021). It is defined as "a deliberate thinking about action with a view to its improvement" (Hatton & Smith, 1995, p. 35).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is necessary to explore pre-service teachers' reflections on their own learning and practice to inform future practice. Adequate preparation influences how pre-service teachers view themselves as professional educators and the way they teach their students (Nwati & Thuthukile, 2021). Within the Omani context, there has been a growing move towards enhancing pre-service teacher education in recent years, particularly in the areas of teaching experience and practical skills (Al-Nofli, 2022;The Education Council, 2018).…”
Section: Introductionmentioning
confidence: 99%